2021
DOI: 10.3892/mmr.2021.11841
|View full text |Cite
|
Sign up to set email alerts
|

SCARA5 suppresses the proliferation and migration, and promotes the apoptosis of human retinoblastoma cells by inhibiting the PI3K/AKT pathway

Abstract: Retinoblastoma (RB) is the most common ocular malignancy that occurs during childhood. Scavenger receptor class A member 5 (SCARA5) is considered to function as an anti-oncogene in several types of malignant tumor. The present study investigated the functional role and underlying mechanism of SCARA5 in human RB cells. Reverse transcription-quantitative PCR and western blotting were used to detect the relative expression levels of SCARA5 in four human RB cell lines. In addition, transfection was performed to ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Disorder of SCARA5 was believed to be involved in the malignancy of multiple tumors such as, Zheng et al found that decreasing SCARA5 promotes Renal Cell Carcinoma proliferation [31]; Wang et al found that SCARA5 could suppress the proliferation and promote the apoptosis of retinoblastoma cells by inhibiting the PI3K/AKT pathway [32]. And some researches revealed that SCARA5 was essential for tumor metastasis and invasion [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Disorder of SCARA5 was believed to be involved in the malignancy of multiple tumors such as, Zheng et al found that decreasing SCARA5 promotes Renal Cell Carcinoma proliferation [31]; Wang et al found that SCARA5 could suppress the proliferation and promote the apoptosis of retinoblastoma cells by inhibiting the PI3K/AKT pathway [32]. And some researches revealed that SCARA5 was essential for tumor metastasis and invasion [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 produced by the cumulus cells activates an autocrine/paracrine FGF2/FGFR loop within the cumulus-oocyte complex to promote oocyte maturation and meiosis [137]. IGF-1 acts through the PI3K/AKT pathway and regulates downstream proteins that may improve ovarian function [138,139]. Thus, growth factors secreted by stem cells can regulate ovarian function and follicular development.…”
Section: Transplantation On Ovarian Follicles and Functionmentioning
confidence: 99%
“…Furthermore, circular RNAs (circRNAs) can also serve as ceRNAs to regulate the proliferation and migration of retinoblastoma cells, such as the circDHDDS/miR-361-3p/WNT3A axis and Circ_0000034/miR-361-3p/ADAM19 axis (47,48). In addition to non-coding RNAs, cyclin-dependent kinase regulatory subunit 1B (CKS1B) downregulation hinders the proliferation, migration, and angiogenesis of retinoblastoma cells through the MEK/ ERK signaling pathway, and an anti-oncogene scavenger receptor class A member 5 (SCARA5) was reported to prevent the proliferation and migration of retinoblastoma cell lines by suppressing the PI3K/AKT signaling pathway (49,50). Studies revealing the mechanisms of the pathogenesis and evolution of retinoblastoma will provide a promising theoretical basis for clinical therapy.…”
Section: Focus In Retinoblastoma Researchmentioning
confidence: 99%